Study of Imam ash-Shaukani View of Najis Hadith is a Requirement for Valid Salat - Muhamad Fikri; Engkos Kosasih; Rizzaldy Satria Wiwaha; Nurudin Mahmudi; Mustain Mustain (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study is to reveal the method used by Imam ash-Shaukānī najis traditions in his book Nailul Auṭār because he is different from most scholars in this regard and the method used is a qualitative literature study with a content analysis approach and takhrij hadith. This study resulted in eight hadiths used by Imam ash-Shaukānī to support his opinion, and some of them are authentic hadiths and some are weak, but he explained his weakness and then he left. So with this the author finds seven methods used by Imam ash-Shaukānī to discuss these najis hadiths in the Nailul Auṭār book, namely al-Jam'u (collecting) these traditions, short mention it for some hadiths, when mention it he only quoted from ulamas before him, did not mention it hadith that had been issued by Imam Bukhari and Muslim, he was very concerned with ushul fiqh, he brought arguments from opponents of his opinion and he mentioned the differences that existed from hadith or fiqh or ushul fiqh.